Reconstruction of Legal Norms for the Execution of Fiduciary Guarantees by Limiting the Involvement of Debt Collectors by Creditors in the Context of Protecting Debtors' Constitutional Rights Based on Contractual Justice - Parisman Sihaloho; Boy Nurdin (Indonesian Journal Publisher, 2026)
This study aims to analyze the weaknesses of the legal construction of the execution of fiduciary guarantees and reconstruct just legal norms in the context of protecting the constitutional rights of debtors. By using normative juridical methods through statutory and conceptual approaches, this study finds that the provisions in Law Number 42 of 1999 concerning Fiduciary Guarantees still contain gaps in norms related to the involvement of debt collectors and open up room for abuse of authority through unilateral execution practices that contradict the principles of due process of law, the principle of good faith, and the guarantee of constitutional rights in the 1945 Constitution. The reconstruction offered emphasizes strict restrictions on the use of third parties, affirmation of execution mechanisms through agreements or court decisions, and the integration of the principles of contractual justice and human rights protection, thus producing a model of legal reform that is fairer, certain, and oriented towards debtor protection.